(untitled) (Global Journal of Computer Science and Technology, 2019)
As the internet is available widely with low cost to connect with the devices day by day. Almost all electronic devices are coming to the market with wi-fi capabilities and sensors built into them, even technology costs also coming down. All of these devices are forming Network by accessing the internet through their wi-fi capabilities. These are creating a perfect IOT storm like smart phones are becoming rocks and penetrating everywhere so the sky is the limit for them. As these all are in the hands of everybody, there is obviously security threats. In this paper, all the possible threats are addressing with possible solutions occurring in these IoT devices. Suggested the Homomorphic Encryption scheme for security in IoT devices.